The Second-Generation Maturation Inhibitor GSK3532795 Maintains Potent Activity Toward HIV Protease Inhibitor–Resistant Clinical Isolates. (1st May 2017) - Ray, Neelanjana; Li, Tianbo; Lin, Zeyu; Protack, Tricia; van Ham, Petronella Maria; Hwang, Carey; Krystal, Mark; Nijhuis, Monique; Lataillade, Max; Dicker, Ira
Abstract : Background: Protease inhibitor (PI)-resistant HIV-1 isolates with primary substitutions in protease ( PR ) and secondary substitutions in Gag could potentially exhibit cross-resistance to maturation inhibitors. We evaluated the second-generation maturation inhibitor, GSK3532795, for activity toward clinical isolates with genotypic and phenotypic characteristics associated with PI resistance (longitudinal). Methods: Longitudinal clinical isolates from 15 PI-treated patients and 7 highly PI-resistant (nonlongitudinal) viruses containing major and minor PI resistance-associated mutations were evaluated for GSK3532795 sensitivity. Phenotypic sensitivity was determined using the PhenoSense Gag/PR assay (Monogram Biosciences) or in-house single- and multiple-cycle assays. Changes from baseline [CFB; ratio of post- to pre-treatment FC-IC50 (fold-change in IC50 versus wild-type virus)] <3 were considered to be within the no-effect level. Results: All nonlongitudinal viruses tested were sensitive to GSK3532795 (FC-IC50 range 0.16–0.68). Among longitudinal isolates, all post-PI treatment samples had major PI resistance-associated mutations in PR and 17/21 had PI resistance-associated changes in Gag. Nineteen of the 21 post-PI treatment samples had GSK3532795 CFB <3. Median (range) CFB was 0.83 (0.05–27.4) [Monogram (11 patients)] and 1.5 (1.0–2.2) [single-cycle (4 patients)]. The 2 post-PI treatment samples showing GSK3532795 CFB >3 (Monogram) were retested using single- and multiple-cycle assays. Neither sample had meaningful sensitivity changes in the multiple-cycle assay. Gag changes were not associated with an increased GSK3532795 CFB. Conclusions: GSK3532795 maintained antiviral activity against PI-resistant isolates with emergent PR and/or Gag mutations. This finding supports continued development of GSK3532795 in treatment-experienced patients with or without previous PI therapy. Abstract : Supplemental Digital Content is Available in the Text.